Pollen morphology of Begonia L. (Begoniaceae) in Nepal - Rajbhandary, Sangeeta; Hughes, Mark; Shrestha, Krishna K. (Bangladesh Journal of Plant Taxonomy, 2012)
The pollen morphology of 28 Begonia species of Nepal has been examined by scanning electron microscopy (SEM). Comparative pollen analysis was made based on size, shape in polar and equatorial views, P/E ratio, aperture, and exine ornamentation. In this study, four types of pollen ornamentation morphology have been identified. Among Nepalese Begonia, B. roxburghii (section Sphenanthera) has the smallest pollen (11.2- 12.8 × 6.4-7.0 ?m) and B. flagellaris (section Diploclinium) has the largest pollen (24.3- 30.6 × 11.4-12.0 ?m). Presence of margo in the pollen ornamentation is a distinguishing character that separates Begonia section Platycentrum from all other sections of Nepalese Begonia. DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13134 Bangladesh J. Plant Taxon. 19(2): 191-200, 2012 (December)